A new model of conceptual design based on Scientific Ontology and intentionality theory. Part I: The conceptual foundation. (March 2015) - Chen, Yong; Zhang, Zhinan; Xie, Youbai; Zhao, Meng
Abstract : This paper is devoted to developing an explicit and complete conceptual foundation for the establishment of a new conceptual design model. Based on Bunge's Scientific Ontology, it first clarifies some concepts (e.g., system, behavior, action) in the objective world. Based on the intentionality theory, a concept of need is then proposed as a concept in the intentional world. Thereafter, an explicit concept of function is elaborated as an intermediate concept between the intentional world and the objective world. Finally, another significant concept related to conceptual design, i.e., abstract principle, is also introduced as an intermediate concept. A detailed discussion demonstrates that the conceptual foundation developed here is more explicit and more complete than those in existing design models. Highlights: With the Scientific Ontology, some basic concepts (e.g., behavior) are clarified. Based on an intentionality theory, the concept of (design) need is clarified. An explicit concept of function is derived for conceptual design research. An explicit concept of abstract principle is given for design research.